Epidemiology of frailty and associated factors among older adults living in rural communities in Taiwan. (March 2020) - Huang, Chung-Yu; Lee, Wei-Ju; Lin, Hui-Ping; Chen, Ren-Chou; Lin, Chi-Hung; Peng, Li-Ning; Chen, Liang-Kung
Highlights: Frailty is the intermediate state between health and disability and is the major focus for disability prevention. Higher cognitive function and education level and better IADL were protective factors against frailty. Poorer performance of TUG, depressive mood, urinary incontinence and risk of malnutrition were all independent risk factors for frailty. Abstract: Frailty is a well-known geriatric syndrome with strong adverse health impact to older people. The socio-economic status and the accessibility of health services in rural communities may increase the risk of frailty. We conducted a cross-sectional study in rural districts of New Taipei City, Taiwan, to explore the epidemiology and associated factors of frailty. Data of 1014 participants (mean age: 78.7 ± 8.0 years, 66.3 % females) were obtained with the prevalence of frailty and pre-frailty 17.6 % and 23.1 %, respectively. The mean Barthel Index was 98.5 ± 5.8, and their mean Instrumental Activities of Daily Living (IADL) were 7.2 ± 1.5. Frail older people tended perform worse in timed up-and-go tests (24.7 % in frailty and 0.4 % in robust). The mean mini-mental state examination (MMSE) score for all participants was 23.3 ± 5.1, but was lower in frail older for around 5 points. Depressive symptoms were more common in frail older persons than robust ones (31.5 % vs 14.3 %), which was similar in the nutritional status. Results of the logistic regression showed that better education, IADL and MMSE scores were protective factors against frailty. The presence of depressive symptoms, urinary incontinence, abnormal performance of TUG, and the presence of the risk for malnutrition were all independent assciated factors for frailty. In conclusion, the prevalence of frailty was higher among older adults living in rural communities that deserves specific public health attentions. Further intervention study covering special needs in rural communities is needed to promote health of older people.